The Difference Between Modal Verbs in Deontic and Epistemic Modality - Winiharti, Menik (Humaniora, 2012)
Modality is always interesting to discuss. Understanding it is crucial for both language teachers and learners. This essay discusses the concept of modality, its types and uses. It has a goal to find the difference between deontic and epistemic modality that is indicated by their modal verbs. It also provides the readers a better understanding of modality, particularly of its types and uses. The result of the analysis shows that in general, deontic modality indicates obligation and permission, while epistemic modality expresses possibility and prediction. However, the difference between deontic and epistemic modality is not a clear cut, since one single modal verb can express both types, and one single proposition can be expressed by more than one modal verb.